PREVALENCE OF FLT-3 MUTATION IN ACUTE MYELOID LEUKAEMIA - Sabir, Kinza; Butt, Nauman Ismat; Akram, Muhammad; Ashfaq, Fahmina; Sajid, Jawayria; Bano, Kausar (Journal of Ayub Medical College Abbottabad, 2021)
Background: FLT-3 mutation is a valuable prognostic marker in patients of AML being related with bad prognosis and poor clinical response to conventional chemotherapeutic agents. Frequency of FLT-3 mutation in AML varies from 25% to 35%. The objective of this study was to determine prevalence of FLT-3 mutation in patients with Acute Myeloid Leukaemia. Methods: This observational cross-sectional Study was conducted in Department of Oncology, Jinnah Hospital Lahore from 1st October 2018 to 31st March 2019. Patients with acute myeloid leukaemia, aged 15-60 years, of both genders were included. After taking consent, demographic data was noted. Three ml of sample of blood was obtained from each patient and sent for detection of FLT-3 mutation. Data was analysed using SPSS version 20.0. Chi square test was applied, p-value <0.05 significant. Results: A total of 180 patients were enrolled in this study. The mean±SD age of patients was 34.72±14.3 years, among which 38.3% were female and 61.7% male. The mean±SD duration of disease was 3.39±2.8 months. The mean±SD haemoglobin level, TLC and platelet counts were 7.2±2.3 g/dl, 30,913±63,573 per cm and 58.6±52.3Ã—103 per cm. The blast cell (%) count was 69.6±19.8. FLT-3 mutation was present in 18.9%. Conclusion: We conclude that FLT-3 mutation to be present in only a minority of patients with Acute Myeloid Leukaemia having no significant association with age, sex, haemoglobin, WBCs and blast counts.